The role of genetic factors in patients with hepatocellular carcinoma and iron overload – a prospective series of 234 patients. (7th November 2015) - Funakoshi, Natalie; Chaze, Iphigénie; Alary, Anne‐Sophie; Tachon, Gaëlle; Cunat, Séverine; Giansily‐Blaizot, Muriel; Bismuth, Michael; Larrey, Dominique; Pageaux, Georges‐Philippe; Schved, Jean‐François; Donnadieu‐Rigole, Hélène; Blanc, Pierre; et al.
Abstract: Background & Aims: Iron overload (IO) in HFE ‐related hereditary haemochromatosis is associated with increased risk of liver cancer. This study aimed to investigate the role of other genes involved in hereditary IO among patients with hepatocellular carcinoma (HCC). Methods: Patients with HCC diagnosed in our institution were included in this prospective study. Those with ferritin levels ≥300 μg/L (males) or ≥200 μg/L (females) and/or transferrin saturation ≥50% (males) or ≥45% (females) had liver iron concentration (LIC) evaluated by MRI. HFE C282Y and H63D mutations were screened. Genetic analyses of genes involved in hereditary IO ( HFE, HJV/HFE2, HAMP, TFR2, SLC40A1, GNPAT ) were performed in patients with increased LIC. Results: A total of 234 patients were included; 215 (92%) had common acquired risk factors of HCC (mainly alcoholism or chronic viral hepatitis). 119 patients had abnormal iron parameters. Twelve (5.1%) were C282Y homozygotes, three were compound C282Y/H63D heterozygotes. LIC was measured by MRI in 100 patients. Thirteen patients with a LIC>70 μmol/g were enrolled in further genetic analyses: two unrelated patients bore the HAMP :c.‐153C>T mutation at the heterozygous state, which is associated with increased risk of IO and severe haemochromatosis. Specific haplotypes of SLC40A1 were also studied. Conclusions: Additional genetic risk factors of IO were found in 18 patients (7.7%) among a large series of 234 HCC patients. Screening for IO and the associated at‐risk genotypes in patients who have developed HCC, is useful for both determining etiologic diagnosis and enabling family screening and possibly primary prevention in relatives.